Microbiological assessment of food contact surfaces in residential college cafeterias at a local University in Malaysia - Siti Shahara Zulfakar; Nur Hidayah Abd. Hamid; Mazrura Sahani (Penerbit Universiti Kebangsaan Malaysia, 2018)
A food premise’s sanitation level can be reflected by the cleanliness of its food contact surfaces. Contaminated food contact surfaces along with poor handling methods by food handlers may increase the risk of foodborne diseases through cross-contamination events. This study aimed to assess the microbiological contamination levels on food contact surfaces of 12 residential college cafeterias in a local university and its correlation with the cafeteria’s premise grade. The presence of selected indicator and pathogenic microorganisms (total viable count (TVC), total coliform, Escherichia coli, Staphylococcus aureus, Salmonella spp., and Shigella spp.) on food contact surfaces were also determined. Cutting boards, knives and utensils (cutleries, bowls and plates) that were used for ready-to-eat food were sampled for this study. The cafeteria’s premise grade was obtained based on the food premise inspection report by the university Health Centre. Three cafeterias have significantly higher (p < 0.05) bacterial counts (TVC) as compared to the international standard (1 log CFU/cm2). E. coli was only found in 2 cafeterias while Salmonella spp. was only detected on 7 of the cafeterias. Cutting boards were identified as the most contaminated food contact surface whereas utensils were the least contaminated. There was only a weak correlation between the microbiological levels on food contact surfaces and the cafeteria’s inspection grade (r = 0.02 p > 0.01). This study demonstrated that the sanitation level of food contact surfaces in the residential college cafeterias was only average. Improvements need to be done to increase the sanitation level of the cafeterias, thus assuring the safety of the food for consumers.